Copal from New Guinea (Tropical Products Department of the Royal Tropical Institute, No. 267) - Spoon W (Verfkronick, 1959)
Copal is the resin collected from the bark of trees belonging to the botanical genius Agathis (family Pinaceae.)
Keywords: Agathis; Pinaceae; Resin